Porphyrins and Metalloporphyrins: Potential Hypoxic Agents - James, B. R. (Hindawi Publishing Corporation, 1996)
Synthetic water-soluble porphyrins and their metalloporphyrin derivatives with Co(III), Cu(II), Ru(II) and Pt(II), containing various functional groups within the meso-positions of the porphyrin, were synthesised and evaluated as hypoxic agents, especially as cytotoxins and radiosensitisers. Cobalt complexes of the porphyrins containing positively charged methylpyridinium groups showed selective toxicity toward hypoxic Chinese Hamster Ovary (CHO) cells. The Co(III) complexes of the cationic and the anionic porphyrins are all weak radiosensitisers toward hypoxic cells, the highest sensitisation enhancement ratio (SER = 1.22, at 50 μM) being with a porphyrin complex containing a cis-arrangement of two nitro and two methylpyridinium meso-substituents. A copper complex of a tetracationic porphyrin showed slight radiosensitisation activity with an SER value of about 1.1. The other metalloporphyrins showed no hypoxic selectivity or radiosensitisation activity. In total, over 50 porphyrin free bases have been synthesised, of which half are water-soluble and have been metallated; thus, the chemistry is now in place for further development of water-soluble hypoxic agents.